Kupffer cell release of platelet activating factor drives dose limiting toxicities of nucleic acid nanocarriers. (January 2021) - Jackson, Meredith A.; Patel, Shrusti S.; Yu, Fang; Cottam, Matthew A.; Glass, Evan B.; Hoogenboezem, Ella N.; Fletcher, R. Brock; Dollinger, Bryan R.; Patil, Prarthana; Liu, Danielle D.; Kelly, Isom B.; Bedingfield, Sean K.; et al.
Abstract: This work establishes that Kupffer cell release of platelet activating factor (PAF), a lipidic molecule with pro-inflammatory and vasoactive signaling properties, dictates dose-limiting siRNA nanocarrier-associated toxicities. High-dose intravenous injection of siRNA-polymer nano-polyplexes (si-NPs) elicited acute, shock-like symptoms in mice, associated with increased plasma PAF and consequently reduced PAF acetylhydrolase (PAF-AH) activity. These symptoms were completely prevented by prophylactic PAF receptor inhibition or Kupffer cell depletion. Assessment of varied si-NP chemistries confirmed that toxicity level correlated to relative uptake of the carrier by liver Kupffer cells and that this toxicity mechanism is dependent on carrier endosome disruptive function. 4T1 tumor-bearing mice, which exhibit increased circulating leukocytes, displayed greater sensitivity to these toxicities. PAF-mediated toxicities were generalizable to commercial delivery reagent in vivo-jetPEI® and an MC3 lipid formulation matched to an FDA-approved nanomedicine. These collective results establish Kupffer cell release of PAF as a key mediator of siRNA nanocarrier toxicity and identify PAFR inhibition as an effective strategy to increase siRNA nanocarrier tolerated dose.